Recognition of Asymptomatic Hypertension in an Urban Emergency Department: Where Are We Now?. (October 2016) - Souffront, Kimberly; Gestal, Christina; Melkus, Gail D'Eramo; Richardson, Lynne
Abstract : Persistently elevated blood pressure ([BP]; hypertension [HTN]) occurs at higher rates in the emergency department ([ED]; 44%) than in the general population (27%) and disproportionately affects black patients and older adults. The American College of Emergency Physicians recommends referral to primary care for HTN confirmation and management when patients are asymptomatic and their BP is persistently elevated (W. Decker, S. Godwin, E. Hess, C. Lenamond, & A. Jagoda, 2006 ). However, adherence to this clinical policy is suboptimal. The purpose of this study was to examine the prevalence of asymptomatic HTN, rates of BP reassessment and referral, and factors associated with it among adult patients who visit the ED and who were discharged a decade after this policy was disseminated. A retrospective chart analysis of adults with an initial BP of 140/90 mmHg or greater and who were discharged was included in the sampling frame. Appropriate bivariate analysis, followed by multivariate regression, was conducted. There were 2, 367 patients who met inclusion criteria, of which 1, 184 patients had asymptomatic HTN. A greater proportion of the sample was male (51.3%), Black (43.2%; p < 0.000), middle aged (μ = 50.2 ± 16), and covered by Medicaid (39.8%). Mean initial BP was 170/88 mmHg. A large proportion of patients with asymptomatic HTN (94.2%) had no previously diagnosed cardiovascular disease (CVD). The BP reassessment rate was 49% (μ = 158/88), and these patients were more likely to have no previously diagnosed CVDs ( p = 0.02). Only 4.6% ( n = 28) of patients with asymptomatic HTN were referred, and these patients were more likely to have no previously diagnosed CVDs ( p = 0.000) and be middle-aged ( p = 0.008). Adherence to follow-up was 100%.